2019
DOI: 10.1038/s41467-019-11821-6
|View full text |Cite
|
Sign up to set email alerts
|

Exposure of an occluded hemagglutinin epitope drives selection of a class of cross-protective influenza antibodies

Abstract: Germinal center (GC) B cells at viral replication sites acquire specificity to poorly immunogenic but conserved influenza hemagglutinin (HA) epitopes. Here, high-throughput epitope mapping of local GC B cells is used to identify conserved HA epitope selecting cross-reactive antibodies that mediate heterosubtypic protection. A distinct feature of this epitope is an occlusion in the naive trimeric HA structure that is exposed in the post-fusion HA structure to occur under low pH conditions during viral replicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 51 publications
1
44
0
Order By: Relevance
“…It has been shown previously that the monomeric LAH is highly immunogenic in mice when incorporated into hepatitis B virus core particles [ 29 , 33 ]. Moreover, post-fusion LAH-specific antibodies have been shown to elicit a durable cross-protective immunity independent of virus neutralization activity [ 34 ]. HA tri-stalk protein was chemically coupled to the surface of purified AP205 or AP-M2e VLPs ( Figure 3 C,D).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been shown previously that the monomeric LAH is highly immunogenic in mice when incorporated into hepatitis B virus core particles [ 29 , 33 ]. Moreover, post-fusion LAH-specific antibodies have been shown to elicit a durable cross-protective immunity independent of virus neutralization activity [ 34 ]. HA tri-stalk protein was chemically coupled to the surface of purified AP205 or AP-M2e VLPs ( Figure 3 C,D).…”
Section: Resultsmentioning
confidence: 99%
“…The combination of multiple conserved influenza antigens into a multivalent single-component AP-M2e/tri-stalk vaccine protected mice from high dose homologous influenza challenge and induced robust heterosubtypic immunity. Since persistent vaccine-induced immunity is a highly desirable feature of a broadly protective influenza vaccine, it should be noted that both the post-fusion LAH-and M2e-based vaccines are known to elicit long-lasting antibody responses [34,55]. Therefore, the long-term immune responses induced by the AP-M2e/tri-stalk vaccine candidate could be the subject of our future research.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Infection, or vaccination with live attenuated influenza viruses, may play a role in the development of cross-reactive antibodies. Broadly neutralizing antibodies are selected at viral replication sites [11] and animal models have shown that sequential infection with IAVs can generate antibodies that are protective against other IAV strains [12]. There is some evidence for cross-reactive responses toward IBVs in animals [13]; however, it is not known how much of this effect is due to B-cell mediated adaptive versus T-cell mediated innate immunity.…”
Section: Introductionmentioning
confidence: 99%